Identifikasi kompetensi manajerial pada level manajemen menengah dalam industri perbankan Indonesia - Jeni Wulandari (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2018)
The purpose if this study is to identify managerial competencies at middle management level in Indonesian banking industry. The study was conducted using a mixed method approach and the competeny menu and database a generic competency model of managersbySpencer & Spencer (1993). The results of the study propose a preliminary managerial competency model that demonstrates general competencies and key competencies for middle managers in banking industry that can be used as a framework in developing competency models in the Indonesian banking industry. This study presents perspectives and methods that provide further support and expansion in competency studies.